(untitled) (Research, Society and Development, 2024)
The process of technological innovation and its strategic planning (TISP) is a complex subject that small enterprises must tackle to achieve effective competitiveness (BC). Both subjects have several factors and actions that more of the small Mexican enterprises do not consider so they have low competitiveness. The objective of this research was to determine the relationship between the TISP and the Competitiveness of SMEs (BC), through the hypothetic-deductive method with a correlation scope, with the analysis of some factors such as the definition and composition of its technological platform, actions of change in it; the generation of capacities, their investment capacity, the agile response to environmental changes, and the analysis of the market and competitors, for the study variables. Throw a research instrument applied to 40 businesses in empirical research we find a 0.904 correlation factor so we propose a model that exhibits the variables and dimensions selected in this research.